Penggunaan E- Wallet Atau Dompet Digital Sebagai Alat Transaksi Pengganti Uang Tunai Bagi UMKM di Kecamatan Banjarmasin Tengah - Chrysilla Zada; Yunita Sopiana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This research is conducted to (1) find out how MSMEs encourage the development of E-wallets or Digital Wallets in Central Banjarmasin district; (2) analyze and find out how the impact of using E-wallet or Digital Wallet as a non-cash payment instrument for SMEs in Central Banjarmasin district.            Research respondents are 30 MSMEs using Digital Wallet in Central Banjarmasin district who could be used for data processing. Data processing uses statistical formulas, data processing, and analysis that emphasize direct observation.            The results of this study showing that MSMEs encourage the development of E-wallets or Digital Wallets. The data indicated that the use of Digital Wallets has increased. Other findings in this study also show that using a Digital Wallet as a non-cash payment instrument for MSMEs aided them is not providing petty cash for change.